Exploring seasonal dynamics of sea spray aerosol bioactivity: Insights into molecular effects on human bronchial epithelial cells - Zixia Liu; Emmanuel Van Acker; Maarten De Rijcke; Filip Van Nieuwerburgh; Colin Janssen; Jana Asselman (Environment International)
Sea spray aerosol (SSA) is a complex mixture of natural substances that can be inhaled by coastal residents. Previous studies have suggested that SSA may have positive effects on human health, but the molecular mechanisms and the factors influencing these effects are poorly understood. In this study, we exposed human bronchial epithelial cells (BEAS-2B) to natural SSA samples, collected monthly using quartz microfiber filters mounted on tripods within 15 m of the waterline, with air drawn through pumps, throughout a one-year period at the Ostend coast, Belgium, and measured cellular gene expression changes using RNA sequencing. To simulate environmentally relevant exposure conditions, SSA extracts were applied at scaled doses equivalent to human alveolar exposure levels (multiplicative factors M = 10, 20, 40, and 80). We found that SSA exposure influenced the expression of genes involved in critical signaling pathways: mTOR, PI3K, Akt, and NF-κB were downregulated, while AMPK was upregulated. Downregulation of mTOR, PI3K, Akt, and NF-κB potentially indicates a protective response against tumor-promoting and inflammatory signals, whereas upregulation of AMPK may confer a beneficial effect on metabolic regulation. The number and direction of differentially expressed genes (DEGs) varied depending on the SSA sampling time and correlated with the phytoplankton density and chemical diversity of the SSA samples. Our results suggest that SSA contains bioactive compounds that may originate from marine algae and modulate cellular processes related to human health. We provide novel insights into the molecular effects of SSA exposure and highlight its potential as a source of natural therapeutics. To our knowledge, this is the first study to expose human lung cells to natural SSA at environmentally relevant levels, presenting a pioneering exploration of seasonal variations in exposure effects.